Cultivate : the six non-negotiable traits of a winning team : a business fable - Bond, Walter, 1969-; Bond, Antoinette (Ascent Audio, 2023)
Cultivate: The Six Non-Negotiable Traits of a Winning Team is a robust and empowering narrative about three corporate team leaders discovering how to build a high-performing team. Over the course of the story, you'll follow these frustrated leaders as they take an introspective look into their own flaws, strengths, fears, habits, and shortcomings and learn firsthand how they impact their teams' cultures. The authors demonstrate how leaders build the cultures they work in and explain why it's up to them to manage and improve it. The book is packed with tried-and-true teamwork fundamentals that are simple to understand and apply. Listeners will also find: explanations of why companies are struggling to recruit, develop, and retain strong teams; practical and applicable tips for employee and team member retention; and explorations of the six traits of high-performing teams that are the signature of all elite business units. A can't-miss journey through the fundamentals of recruiting, building, and maintaining a high-performing team in your own organization, Cultivate is a valuable resource for executives, managers, and other business leaders struggling to adapt to the human resources and retention challenges posed by the new economy. In business, organizations are totally dependent on a leader's ability to CULTIVATE!